Preface of the "the Development of Sustainable and Accessible Infrastructure and Modelling" (DSAIM-2021) - Campisi, Tiziana; Acampa, Giovanna; Tanbay, Nurten Akgün; Torrisi, Vincenza (American Institute of Physics Inc., 2022)
[Abstract Not Available]
International Conference of Computational Methods in Sciences and Engineering 2021, ICCMSE 2021 -- 2021-09-04 through 2021-09-07 -- Heraklion -- 184643